The Mediating Role of Social Support in the Relationship Between Parenting Styles and Adolescent Drug Abuse Identification - Liu, Li; Meng, Weijie; Liu, Bingyuan (Frontiers in Psychology, 2022)
Adolescent drug abuse is a social issue of global concern, causing a serious burden of diseases for individuals, families and society. To design effective prevention and intervention strategies for adolescent drug abusers, the predictive factors associated with drug abuse must be quantified and assessed. This study explores the similarities and differences between the parenting styles of adolescent drug abusers and non-drug abusers and applies a structural equation model to analyze the mechanisms involved between parenting styles, social support and adolescent drug abuse identification. Data were derived from adolescent drug abusers (n = 363) and non-drug abusers (n = 229) between the ages of 18 and 35 in China, and the data were collected and analyzed by SPSS 26 and AMOS 24. The results show that parenting styles significantly predict adolescent drug abuse identification, and different parenting styles have different influencing mechanisms, which further indicates that poor parenting styles are a risk factor for adolescent drug abuse. Additionally, social support plays a mediating role between parenting styles and drug abuse identification (χ2/df = 4.52, CFI = 0.939, TLI = 0.914, RMSEA = 0.077, IFI = 0.939, PCFI = 0.671). The specific pathways involved are as follows: Paternal parenting style  Social support  Drug abuse identification and Maternal parenting style  Social support  Drug abuse identification. However, beyond this, the mediation model of social support shows good adaptability and stability between adolescent drug abusers and non-drug abusers. Since parenting styles and social support are important predictors of adolescent drug abuse, the importance of integrating family-social support antidrug programs into adolescent prevention and intervention strategies should be considered.